Effects of road transportation on metabolic and immunological responses in Holstein heifers. (18th April 2016) - Kang, Hyeok‐Joong; Lee, In Kyu; Piao, Min‐Yu; Kwak, Chae‐Won; Gu, Min Jeong; Yun, Cheol Heui; Kim, Hyun‐Jin; Ahn, Hyeon‐Ju; Kim, Hee‐Bal; Kim, Gyeom‐Heon; Kim, Soo‐Ki; Ko, Jong‐Youl; et al.
Abstract: This study examined the effects of road transportation on metabolic and immunological responses in dairy heifers. Twenty Holstein heifers in early pregnancy were divided into non‐transported (NT; n = 7) and transported (T; n = 13) groups. Blood was collected before transportation (BT), immediately after transportation for 100 km (T1) and 200 km (T2), and 24 h after transportation (AT). The T heifers had higher ( P < 0.05) blood cortisol and non‐esterified fatty acid concentrations after T1 and T2 than did NT heifers. By contrast, the T heifers had lower ( P < 0.05) serum triglyceride concentrations after T1 and T2 than had the NT heifers. The serum cortisol and triglyceride concentrations returned (P > 0.05) to the BT concentrations at 24 h AT in the T heifers. The granulocyte‐to‐lymphocyte ratio and the percentage of monocytes were higher ( P < 0.05) after T2 in the T heifers than in the NT heifers, suggesting that transportation stress increased the numbers of innate immune cells. T heifers had higher ( P < 0.01) plasma haptoglobin concentrations than NT heifers 24 h AT. In conclusion, transportation increased cortisol secretion and was correlated with increased metabolic responses and up‐regulation of peripheral innate immune cells in dairy heifers.